2014
DOI: 10.1186/s12879-014-0595-z
|View full text |Cite
|
Sign up to set email alerts
|

Mold contamination in a controlled hospital environment: a 3-year surveillance in southern Italy

Abstract: BackgroundEnvironmental monitoring of airborne filamentous fungi is necessary to reduce fungal concentrations in operating theaters and in controlled environments, and to prevent infections. The present study reports results of a surveillance of filamentous fungi carried out on samples from air and surfaces in operating theaters and controlled environments in an Italian university hospital.MethodsSampling was performed between January 2010 and December 2012 in 32 operating theaters and five departments with hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
28
3
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 26 publications
5
28
3
1
Order By: Relevance
“…The occurrence of bacteria in hospitals has been commonly related to some possible sources of dissemination: bottle soap [18], hands of healthcare professionals [19], gloves and gowns [20], mobile phones [21] paper money and coins [22]. Aspergillus fumigatus was found to be predominant fungi with frequency occurrence of 36.84%, this correlate with the report of Cagginao et al [23] who reported that Aspergillus fumigatus was the most commonly isolated [68.5%].…”
Section: Discussionsupporting
confidence: 68%
“…The occurrence of bacteria in hospitals has been commonly related to some possible sources of dissemination: bottle soap [18], hands of healthcare professionals [19], gloves and gowns [20], mobile phones [21] paper money and coins [22]. Aspergillus fumigatus was found to be predominant fungi with frequency occurrence of 36.84%, this correlate with the report of Cagginao et al [23] who reported that Aspergillus fumigatus was the most commonly isolated [68.5%].…”
Section: Discussionsupporting
confidence: 68%
“…High humidity levels support microbial growth due to moisture absorption by building materials . Pathogenic microorganisms can adhere quickly to moist and slick or damaged walls and ceilings which can affect patient and staff well‐being …”
Section: Indoor Environmental Parameters Impacting Patient Outcomesmentioning
confidence: 99%
“…Studies conducted by Shams-Ghahfarokhi et al (2014), Caggiano et al (2014) andChang et al (2014) confirmed that the environmental monitoring of airborne filamentous fungi is necessary to reduce fungal concentrations in operating theaters and in controlled environments, to prevent infections. According to Chang et al (2014), in the tentative to reduce the environmental contamination by fungi, recommended that a standardized protocol for the sampling collection and culture is necessary in hospital institutions to verify the air quality.…”
Section: Discussionmentioning
confidence: 99%
“…There are several reports in hospitalized patients affected by mycoses caused by airborne filamentous fungi present in the environment (Peckham et al, 2016;Caggiano et al, 2014;Shams-Ghahfarokhi et al, 2014), meanwhile in Brazil, few studies (Flores and Onofre, 2010;Lobato et al, 2009;Carmo et al, 2007;Martins-Diniz et al, 2005) characterizing the airborne fungi microbiota in the ICUsʼ environment, being an important knowledge for control strategies. The aim of this study was the isolation and identification of airborne fungi in an ICU from the University Hospital of Pelotas (RS -Brazil).…”
Section: Introductionmentioning
confidence: 99%